Electrode material additive, preparation method thereof, pole piece and secondary battery

By using the first and second polymer molecules to form mechanical interlocking chains in the electrode material, the problem of insufficient toughness of the electrode sheet is solved, flexibility and stability are improved, battery life is extended, and safety is improved.

CN119542423APending Publication Date: 2025-02-28SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411758044.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

While the existing electrode material additives increase the energy density of secondary batteries, they also lead to insufficient toughness of the electrode sheet and are prone to cracking, which affects the stability and life of the battery.

Method used

An electrode material additive is adopted, which consists of a first polymer molecule and a second polymer molecule, and a mechanical interlocking chain is formed through topological bonding of the first coupling segment and the second coupling segment to improve the flexibility and stability of the electrode sheet.

Benefits of technology

Through the structure of mechanical interlocking chains, the flexibility and stability of the pole sheet are improved, cracking is prevented, the life of the battery is extended, and the safety of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542423A_ABST
    Figure CN119542423A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode material additive and a preparation method thereof, a pole piece and a secondary battery, the electrode material additive comprises a first polymer molecule and a second polymer molecule, the first polymer molecule comprises a first matching chain segment and a first flexible chain segment which are connected, the second polymer molecule comprises a second matching chain segment and a second flexible chain segment which are connected, the second coordination chain segment comprises a cyclic group, and the second coordination chain segment is topologically bonded with the first coordination chain segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanical interlocking chain. The electrode material additive can solve the problem of cracking caused by insufficient toughness of a pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and in particular to an electrode material additive and a preparation method thereof, an electrode sheet and a secondary battery. Background Art

[0002] With the rapid development of the global new energy industry, the attention to the energy density of secondary batteries is also increasing. In order to improve the energy density of secondary batteries, the development of electrode material additives provides a good direction for progress. Electrode material additives can not only improve the solid content and processability of slurry during slurry manufacturing, but also reduce the use of NMP and reduce the energy consumption cost of coating and drying, which brings good news to the energy density of secondary batteries.

[0003] However, the development of electrode material additives still cannot strip away the “copy and paste” of polymers in traditional dispersants, and the introduction of polymer materials is bound to lead to embrittlement of the pole pieces, especially when thickly coated. Due to insufficient toughness and flexibility, the pole pieces may crack, leak, or peel off when wound or folded, affecting the stability and durability of the coating, and further affecting the safety and life of the battery. In addition, when highly expandable materials such as silicon oxygen or silicon carbon are used as the negative electrode, during the battery cycle, the expansion of the structure is often more likely to cause cracking of the SEI film and the binder, which also directly affects the stability, safety and life of the battery. Therefore, how to provide an electrode material additive that can improve the flexibility of the pole piece has become the key. Summary of the invention

[0004] The purpose of the present application is to provide an electrode material additive and a preparation method thereof, an electrode piece and a secondary battery, wherein the electrode material additive can solve the problem of cracking caused by insufficient toughness of the electrode piece.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides an electrode material additive, comprising a first polymer molecule and a second polymer molecule, wherein the first polymer molecule comprises a first mating segment and a first flexible segment connected to each other, and the second polymer molecule comprises a second mating segment and a second flexible segment connected to each other, wherein the second mating segment is cyclic, and the second mating segment is topologically bonded to the first mating segment through the cyclic group so that the first polymer molecule and the second polymer molecule form a mechanically interlocked chain.

[0007] In one embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are the same, the molecular structures of the first flexible segment and the second flexible segment are the same, the two ends of the first flexible segment are respectively connected to the first mating segment and the second mating segment, and multiple first polymer molecules or multiple second polymer molecules form a mechanical interlocking chain connected in sequence.

[0008] In one embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are different, the two ends of the first flexible segment are respectively connected to one of the first mating segments, the two ends of the second flexible segment are respectively connected to one of the second mating segments, and the first polymer molecule and the second polymer molecule form a periodically connected mechanical interlocking chain.

[0009] In one embodiment, the first polymer molecule further includes a first self-repairing segment, and the first self-repairing segment is connected to an end of the first flexible segment facing away from the first matching segment.

[0010] In one embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are different, and the second polymer molecule further includes a second self-repairing segment, which is connected to an end of the second flexible segment facing away from the second mating segment.

[0011] In one embodiment, the first coordinating segment includes a nitrogen-containing group, the second coordinating segment includes a crown ether group, the crown ether group is arranged around the periphery of the nitrogen-containing group, and the first self-healing segment and / or the second self-healing segment contain an XX bond, wherein X is any element in the VIA group.

[0012] In one embodiment, the first cooperating segment includes a steric end group, which is used to end-cap the first polymer molecule, and the cyclic group is the end group of the second polymer molecule, which is used to end-cap the second polymer molecule.

[0013] In one embodiment, the electrode material additive has a weight average molecular weight of 500 to 2500.

[0014] In one embodiment, the number of repeating units in the first flexible segment is 4-46.

[0015] In one embodiment, the number of repeating units in the second flexible segment is 4-46.

[0016] In a second aspect, the present application provides a method for preparing an electrode material additive, the preparation method comprising the following steps: preparing a mixed liquid having a first polymer molecule precursor, wherein the first polymer molecule precursor comprises a first coordinating segment and a first flexible segment; adding a second polymer molecule or a second polymer molecule precursor to the mixed liquid, wherein both the second polymer molecule and the second polymer molecule precursor comprise a second coordinating segment and a second flexible segment, wherein the second coordinating segment is cyclic, and the second coordinating segment is topologically bonded to the first coordinating segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanically interlocking chain to obtain the electrode material additive.

[0017] In a third aspect, the present application provides an electrode sheet, comprising an electrode material and the electrode material additive as described in the first aspect, wherein the electrode material is a positive electrode material or a negative electrode material.

[0018] In a fourth aspect, the present application provides a secondary battery, comprising the electrode sheet as described in the third aspect, or the secondary battery comprises the electrode material additive as described in the first aspect.

[0019] The electrode material additive provided by the present application includes a polymer molecule having a first matching segment and a second matching segment at the same time, and two adjacent polymer molecules (i.e., a first polymer molecule and a second polymer molecule) are connected by the topological bonding of the first matching segment and the second matching segment, and the first polymer molecule passes through the cyclic group in the second polymer molecule, so that the first polymer molecule and the second polymer molecule form a non-chemically bonded mechanical interlocking mode, and the mechanical interlocking of the first polymer molecule and the second polymer molecule not only maintains the dynamic motion of the first polymer molecule (free sliding in the case of mechanical interlocking of the ring structure), has efficient energy dissipation characteristics, greatly improves flexibility, and maintains high stability and strength without destroying covalent bonds. At the same time, the mechanical interlocking of the first polymer molecule and the second polymer molecule, on the one hand, avoids the disadvantage that the molecular chain rotation of the electrode material additive is hindered due to the large molecular weight, and then the flexibility is reduced, and on the other hand, it also greatly improves the problem of insufficient toughness and susceptibility to electrolyte corrosion caused by the short chain of the electrode material additive. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1is a schematic structural diagram of an electrode material additive in one embodiment;

[0022] Figure 2 is a flow chart of the preparation of an electrode material additive in one embodiment;

[0023] Figure 3 is a schematic structural diagram of an electrode material additive in another embodiment;

[0024] Figure 4 is a flow chart of the preparation of an electrode material additive in another embodiment;

[0025] Figure 5 is a flow chart for preparing a second polymer molecule in one embodiment;

[0026] Figure 6 is an infrared spectrum of the electrode material additive in Example 1;

[0027] Figure 7 These are actual pictures of the electrode sheets prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0029] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0030] It should be noted that the "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0031] All steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.

[0032] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0033] The electrode material additive of the present application can be added to the electrode material, and the electrode material includes a positive electrode material or a negative electrode material. In a specific embodiment, the electrode material additive can be added to the slurry of the electrode material of the aqueous system or the organic solvent system. The function of the electrode material additive is to increase the flexibility of the electrode piece made of the electrode material, improve the curling effect of the electrode piece, and prevent the electrode piece from cracking.

[0034] This application provides an electrode material additive, please refer to Figure 1 .

[0035] In one embodiment, the electrode material additive includes a first polymer molecule 100 and a second polymer molecule 200, and the first polymer molecule 100 and the second polymer molecule 200 have the same molecular structure. Specifically, the electrode material additive in this embodiment includes a plurality of polymer molecules with the same molecular structure, and the polymer molecules are connected end to end through topological bonding.

[0036] In one embodiment, the first polymer molecule 100 includes a first mating segment and a first flexible segment connected to each other, and the second polymer molecule 200 includes a second mating segment and a second flexible segment connected to each other, the second mating segment includes a cyclic group, and the second mating segment is topologically bonded to the first mating segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanically interlocking chain.

[0037] Specifically, the first coordinating segment and the second coordinating segment realize topological bonding through complexation reaction, wherein topological bonding means that after the first coordinating segment and the second coordinating segment are connected through complexation reaction and both are deionized, the first polymer molecule and the second polymer molecule are connected together through the intermolecular force generated between the first coordinating segment and the second coordinating segment.

[0038] Therefore, when the second matching segment includes a cyclic group, the second matching segment is arranged around the periphery of the first polymer molecule 100 through the cyclic group, and the cyclic group can move along the first flexible segment, so that the second polymer molecule moves relative to the first polymer molecule. In addition, the cyclic group can also be used as an end group to provide a capping effect.

[0039] The electrode material additive provided by the present application includes a polymer molecule having both a first matching segment and a second matching segment, and two adjacent polymer molecules (i.e., a first polymer molecule 100 and a second polymer molecule 200) are connected by the topological bonding of the first matching segment and the second matching segment, and the first polymer molecule 100 passes through the cyclic group in the second polymer molecule 200, so that the first polymer molecule 100 and the second polymer molecule 200 form a non-chemically bonded mechanical interlocking mode, and the mechanical interlocking of the first polymer molecule 100 and the second polymer molecule 200 not only maintains the dynamic movement of the first polymer molecule 100 (free sliding under the condition of mechanical interlocking of the ring structure), has efficient energy dissipation characteristics, greatly improves flexibility, and maintains high stability and strength without destroying covalent bonds. At the same time, the mechanical interlocking of the first polymer molecule 100 and the second polymer molecule 200, on the one hand, avoids the disadvantage that the molecular chain rotation of the electrode material additive is hindered due to the large molecular weight, and then the flexibility is reduced, and on the other hand, it also greatly improves the problem that the electrode material additive chain is short, resulting in insufficient toughness and susceptibility to electrolyte corrosion.

[0040] In one embodiment, the first coordination segment includes a nitrogen-containing group, and the second coordination segment includes a crown ether group, which is arranged around the periphery of the nitrogen-containing group. The nitrogen-containing group and the crown ether group are connected together by topological bonding after complexation reaction. Specifically, the nitrogen-containing group includes an amino group (-NH2) or an imino group (-NH-); the crown ether group is a macrocyclic polyether containing multiple -O-CH2- structural units in the molecule, and the crown ether group is the cyclic group mentioned above. It can be understood that the crown ether group is cyclic, so the chain part containing the nitrogen-containing group in the first polymer molecule 100 can pass through the crown ether group, and the crown ether group has multiple -O-CH2- structural units, so a high-density electron cloud will be formed in the crown ether. The biggest feature of the crown ether is that it can complex with positive ions, especially with alkali metal ions, and complex with different metal ions depending on the size of the ring, so the nitrogen-containing group can also complex with the crown ether group to achieve topological bonding.

[0041] In one embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are the same, the molecular structures of the first flexible segment and the second flexible segment are the same, the two ends of the first flexible segment are respectively connected to the first matching segment and the second matching segment, and multiple first polymer molecules or multiple second polymer molecules form a mechanical interlocking chain connected in sequence.

[0042] Specifically, the first flexible segment includes a plurality of first repeating units connected in sequence, the first matching segment is connected to one end of the first repeating unit, and the first repeating unit includes an ether bond and / or an ester group. In a specific embodiment, the first flexible segment may include one or more of a polyethylene glycol segment, a polypropylene glycol segment, a polytetrahydrofuran segment, a polyglycolide segment, a polylactic acid segment, a glycolide-lactide copolymer segment, a polycaprolactone segment, etc., wherein the number of repeating units containing an ester group may be 2 to 25.

[0043] In a specific embodiment, taking the first flexible segment including a polyethylene glycol segment as an example, the molecular formula of the polyethylene glycol segment is -(CH2CH2O) n -, wherein the first repeating unit refers to (CH2CH2O). It should be explained that the present application does not limit the specific type of the first repeating unit in the first flexible segment, and chain polymers including ether bonds and / or ester groups can be used as the first flexible segment in the present application.

[0044] Furthermore, the molecular structure of the first flexible segment and the second flexible segment is the same, so the second flexible segment can include all the structural components of the first flexible segment mentioned above, so the second flexible segment can refer to the first flexible segment and will not be described in detail here.

[0045] The present application introduces the first flexible segment into the first polymer molecule 100 to improve the overall compliance of the electrode material additive. This is because the first flexible segment has a small internal rotation steric hindrance and good compliance, and the flexibility of the ether bond or ester group is greater than that of the carbon-carbon bond; secondly, the side chain symmetry of the first flexible segment is good, which can further improve the flexibility; in addition, the ether bond or ester group in the first flexible segment can form more hydrogen bonds with the metal ions in the electrode material, and has strong adhesion to the electrode material. The electrode material additive has the function of an adhesive, which not only makes it difficult for the electrode material to fall off the current collector, but also reduces the amount of adhesive in the electrode slurry.

[0046] In one embodiment, the first polymer molecule further includes a first self-repairing segment, which is connected to one end of the first flexible segment away from the first matching segment. Specifically, the first self-repairing segment has a self-repairing property, so the first self-repairing segment has good interface self-healing ability and can be used to repair solid interface defects in the electrode material, such as cracks, thereby improving the solid interface structure stability in the electrode material.

[0047] The present application introduces a first self-repairing segment with self-repairing properties into the polymer molecule, which not only increases the main chain length of the first polymer molecule 100, but also enables the first self-repairing segment to realize a self-repairing function when the main chain of the first polymer molecule 100 is broken by an external force, thereby further preventing the electrode from cracking during the electrode material coating process.

[0048] In one embodiment, the second matching segment in the first polymer molecule 100 is connected to the first self-repairing segment. Specifically, when the molecular structures of the first polymer molecule 100 and the second polymer molecule 200 are the same, the first polymer molecule 100 also includes the second matching segment, and the second polymer molecule 200 also includes the first matching segment. Therefore, in the first polymer molecule 100 (the second polymer molecule 200), the first matching segment, the first flexible segment, the first self-repairing segment and the second matching segment connected in sequence are included.

[0049] In one embodiment, the first coordination segment includes a steric end group, which is used to end-cap the first polymer molecule, and the cyclic group is the end group of the second polymer molecule, which is used to end-cap the second polymer molecule.

[0050] The present application uses a steric unit to terminate the first polymer molecule 100, and after the steric monomer and the flexible chain monomer react, a first coordinated segment with cationic characteristics is formed at the position where the two are combined, so that the first polymer molecule 100 can form an interlocking structure with a tail connection with the second polymer molecule.

[0051] In this embodiment, the molecular structure formula of the first polymer molecule 100 (or the second polymer molecule 200) is [SH]-[EG1] n1 -[SS1]-[CC], where [SH] is the first matching segment, [EG1] n1 is the first flexible segment, EG1 is the first repeating unit, [SS1] is the first self-repairing segment, [CC] is the second matching segment, SH includes a steric end group, and SH and EG1 are connected by a nitrogen-containing group. In a specific embodiment, the first polymer molecule 100 (or the second polymer molecule 200) is copolymerized by a steric monomer, a flexible chain monomer, a first self-repairing monomer and a cyclic monomer. Among them, the steric monomer includes a steric end group, the flexible chain linear monomer includes the first flexible segment, the first self-repairing monomer includes the first self-repairing segment, and the cyclic monomer includes the second matching segment; the steric monomer and the flexible chain linear monomer react to form the first matching segment.

[0052] In one embodiment, the weight average molecular weight of the electrode material additive is 500 to 2500. Optionally, the weight average molecular weight of the electrode material additive can be 500, 1000, 1500, 2000, 2500. Controlling the molecular weight of the electrode material additive within the above range can avoid the decomposition of the additive and provide a suitable molecular slip length, thereby achieving the characteristics of high flexibility. Because, after the first polymer molecule 100 and the second polymer molecule 200 are mechanically interlocked, the molecular sliding between the two is mainly affected by the molecular weight of the second polymer molecule 200 and the chain length of the first polymer molecule 100 (of course, when the two are the same, the molecular weight and chain length of the polymer molecule need to be controlled). If the molecular weight is too large, it corresponds to a long molecular chain, and the internal rotation steric hindrance of the molecular chain is large, the free movement is affected, and the molecular flexibility is reduced. While maintaining a certain molecular weight range, the internal rotation steric hindrance of the second polymer molecule 200 is small, which also makes the sliding effect in the main chain of the first polymer molecule 100 better, and the energy dissipation characteristics are strong when the pole piece is subjected to bending or stretching external forces, and the flexibility effect is better. If the molecular weight is too small, the polymer molecules are easily dissolved or decomposed by the electrolyte.

[0053] In one embodiment, the number of repeating units in the first soft segment is 4 to 46, that is, [EG1] in the above embodiment. n1 4≤n1≤46. Optionally, the number of repetitions of the first repeating unit may be 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 46; preferably, the number of repetitions of the first repeating unit may be 21-22.

[0054] In one embodiment, the first self-repairing segment comprises an XX bond, wherein X is any element in group VIA. In a specific embodiment, the first self-repairing segment comprises an SS bond (disulfide bond), a Se-Se bond (diselenide bond), and the like.

[0055] In one embodiment, the amount of the electrode material additive added to the electrode material is 0.01% to 0.3%. Optionally, the amount of the electrode material additive added to the electrode material can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%. The electrode material additive can improve the crack resistance and flexibility of the thick coating of the electrode piece, and will not affect the content of the electrode material.

[0056] This application provides a method for preparing an electrode material additive. Please refer to Figure 2 .

[0057] In one embodiment, the preparation method of the electrode material additive comprises the following steps:

[0058] Step A10, preparing a mixed solution containing a first polymer molecular precursor, wherein the first polymer molecular precursor comprises a first coordination segment and a first flexible segment.

[0059] Step A20, adding a second polymer molecule precursor to the mixed liquid, the second polymer molecule precursor comprising a second cooperating segment and a second flexible segment, the second cooperating segment comprising a cyclic group, the second cooperating segment being topologically bonded to the first cooperating segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanically interlocking chain to obtain an electrode material additive.

[0060] Specifically, in this embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are the same, so the electrode material additive includes a plurality of polymer molecules with the same molecular structure, and the polymer molecules are connected together end to end through complexation reaction and topological bonding.

[0061] In one embodiment, in step A10, a mixed solution having a first polymer molecule precursor is prepared, specifically comprising: adding a flexible chain monomer and a steric hindered monomer to a solvent for reaction, and controlling the solvent to be acidic, and stirring under a protective gas to obtain a first polymer molecule precursor comprising a first coordination segment and a first flexible segment. The flexible chain monomer comprises a first flexible segment and an active group, and the steric hindered monomer comprises a steric end group and an active group. The flexible chain monomer and the steric hindered monomer react to obtain a first polymer molecule precursor, specifically, the active group of the flexible chain line reacts with the active group of the steric hindered monomer to form a first coordination segment.

[0062] In one embodiment, in step A10, the flexible chain monomer includes carboxyl and amino terminated polymers, including but not limited to carboxyl and amino terminated polyethylene glycol (NH2-PEG-COOH), carboxyl and amino terminated polypropylene glycol (NH2-PPG-COOH), carboxyl and amino terminated polytetrahydrofuran (NH2-PTMG-COOH), etc. In other embodiments, the flexible chain monomer may also be an amino and other group terminated polymer, not limited to carboxyl and amino terminated polymers. It is understood that the amino termination is to utilize the amino group to form a nitrogen-containing group, and the carboxyl group (or another group) at the other end is to enable the first polymer molecule precursor to form a long chain.

[0063] In other embodiments, in step A10, the flexible chain monomer may also include amino-terminated polyether (NH2-POP), polyester (NH2-PET), polyurethane (NH2-PU), polysiloxane, and the like.

[0064] In one embodiment, the weight average molecular weight of the flexible chain monomer may be 200 to 2000, and the number of repetitions of the first repeating unit in the flexible chain monomer may be 4 to 46. Taking carboxyl and amino terminated polyethylene glycol as an example, its chemical formula is COOH-(CH2CH2O) n1 -CH2CH2-NH2, where (CH2CH2O) n1 [EG1] in the above embodiment n1 .

[0065] In one embodiment, in step A10, the hindered monomer contains an aldehyde group or a ketone carbonyl group, specifically including but not limited to any one of benzaldehyde, p-methylbenzaldehyde, benzophenone, acetophenone, and propiophenone. The aldehyde group or ketone carbonyl group in the hindered monomer can react with the amino group in the flexible chain monomer to obtain a main chain terminated with a sterically hindered end group containing an imino group.

[0066] In one embodiment, in step A10, the solvent of the mixed solution can be water. After adding the flexible chain monomer to water, the solution pH can be adjusted to 2-3 using hydrochloric acid and ammonium hexafluorophosphate, stirred at 50° C.-80° C. in an inert atmosphere, and then the steric monomer is added to react with the flexible chain monomer for 2 h-4 h.

[0067] In one embodiment, in step A20, a second polymer molecule precursor is added to the mixed liquid, specifically including: adding the second polymer molecule precursor to the mixed liquid after the reaction in step A10 is completed, and the second coordinating segment in the second polymer molecule precursor is induced by the first coordinating segment, and the cyclic group penetrates from the main chain of the first polymer molecule and is topologically bonded to the first coordinating segment.

[0068] In one embodiment, in step A20, the second polymer molecule precursor is the cyclic monomer in the above embodiment, comprising a second coordination segment and an active group, wherein the active group is used to connect to the other end of another group of first polymer molecules (i.e., the end away from the steric end group), and the active group can be a carboxyl group. Therefore, when the first polymer molecule and the second polymer molecule are the same, the first polymer molecule and the second polymer molecule form a mechanical interlocking chain connected end to end.

[0069] In one embodiment, in step A20, the second coordinating segment is a crown ether group, and the second polymer molecule precursor is a crown ether derivative, specifically including but not limited to one or more of 4-carboxybenzo-12-crown ether-4, 4-carboxybenzo-15-crown ether-5, 4-carboxybenzo-18-crown ether-6, 4-carboxybenzo-21-crown ether-7, 1,10-diaza-18-crown ether 6, 4-carboxybenzo-1,7,13-triaza-18-crown ether-6, and 4-carboxybenzo-4,10-diaza-12-crown ether-4.

[0070] In one embodiment, in step A20, after adding the second polymer molecule precursor to the mixed liquid, it also includes: adding the first self-healing monomer to the mixed liquid after the reaction is completed, and the first self-healing monomer reacts with the second polymer molecule precursor and the first polymer molecule precursor respectively to obtain the first polymer molecule and the second polymer molecule connected end to end.

[0071] In one embodiment, in step A20, the first self-healing monomer comprises a first self-healing segment and an active group connected to both ends of the first self-healing segment, wherein the first self-healing segment comprises an XX bond, wherein X is any element in the VIA group. In a specific embodiment, the first self-healing segment comprises an SS bond (disulfide bond), a Se-Se bond (diselenide bond), etc.; the active group may be a hydroxyl group, and in a specific embodiment, the first self-healing monomer comprises bis(2-hydroxyethyl) disulfide (HOCH2CH2S-SCH2CH2OH).

[0072] It needs to be explained that the first self-healing monomer reacts with the second polymer molecule precursor and the first polymer molecule precursor respectively, and the second polymer molecule precursor contains exposed carboxyl active groups (carboxyl groups), and the first polymer molecule precursor also contains exposed active groups (carboxyl groups), so the active groups (hydroxyl groups) at both ends of the first self-healing monomer can undergo esterification reactions with the two respectively to obtain ester groups.

[0073] In one embodiment, in step A20, the self-assembly time of the first polymer molecular precursor and the second polymer molecular precursor may be 0.5 h to 3 h.

[0074] In one embodiment, in step A20, an appropriate amount of concentrated sulfuric acid / concentrated phosphoric acid may be added at the same time as the first self-healing monomer is added, and the precursor in the mixed solution is allowed to fully react for 4 to 6 hours.

[0075] In one embodiment, in step A20, after the reaction is completed, an appropriate amount of dichloroethane is added to the mixed solution for extraction, the organic phases are combined, dried with anhydrous sodium sulfate or anhydrous magnesium sulfate, and finally spin-dried at 80° C. to 100° C. to obtain the electrode material additive.

[0076] The electrode material additive prepared by the above-mentioned preparation method can be applied to aqueous or organic solvents of electrode materials to improve the flexibility of the electrode and prevent the cracking of the electrode. The multiple polymer molecules in the electrode material additive are linearly connected head to tail through topological bonding, the tail end of the previous polymer molecule (first polymer molecule) is topologically bonded to the head end of the next polymer molecule (second polymer molecule), and the second polymer molecule can slide freely on the flexible main chain of the first polymer molecule (molecular pulley) without falling off, thereby forming a mechanically interlocked linear necklace structure.

[0077] This application provides another electrode material additive, please refer to Figure 3 .

[0078] In one embodiment, the electrode material additive includes a first polymer molecule 100 and a second polymer molecule 200, and the molecular structures of the first polymer molecule 100 and the second polymer molecule 200 are different. Specifically, in the electrode material additive in this embodiment, a plurality of first polymer molecules 100 and a plurality of second polymer molecules 200 are included, and both ends of the second polymer molecule 200 are respectively connected to a group of independent first polymer molecules 100 through topological bonding. Of course, it can also be understood that both ends of the first polymer molecule 100 are respectively connected to a group of independent second polymer molecules 200 through topological bonding.

[0079] In one embodiment, the first polymer molecule 100 includes two first matching segments, two first flexible segments and a first self-repairing segment. Therefore, two nitrogen-containing groups are included in the first polymer molecule 100. In addition, both ends of the first polymer molecule 100 are respectively terminated by steric end groups. Therefore, the first polymer molecule 100 includes the first matching segment, the first flexible segment, the first self-repairing segment, the first flexible segment and the first matching segment connected in sequence.

[0080] In one embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are different, the molecular structures of the first flexible segment and the second flexible segment may be the same or different, the two ends of the first flexible segment are respectively connected to a first mating segment, and the two ends of the second flexible segment are respectively connected to a second mating segment, and the first polymer molecule and the second polymer molecule form a periodically connected mechanical interlocking chain.

[0081] Specifically, the second flexible segment includes a plurality of second repeating units connected in sequence, the second matching segment is connected to one end of the second repeating unit, and the second repeating unit includes an ether bond and / or an ester group. In a specific embodiment, the second flexible segment may include one or more of a polyethylene glycol segment, a polypropylene glycol segment, a polytetrahydrofuran segment, a polyglycolide segment, a polylactic acid segment, a glycolide-lactide copolymer segment, a polycaprolactone segment, etc.

[0082] In a specific embodiment, the molecular structure of the second flexible segment and the first flexible segment may be the same, and the second repeating unit may be the same as the first repeating unit. For example, the second flexible segment includes a polyethylene glycol segment, and the molecular formula of the polyethylene glycol segment is -(CH2CH2O) n -, wherein the second repeating unit refers to (CH2CH2O). It should be explained that the present application does not limit the specific type of the second repeating unit in the second flexible segment, and chain polymers including ether bonds and / or ester groups can be used as the second flexible segment in the present application. Of course, in other embodiments, the second repeating unit may be different from the first repeating unit, for example, the second flexible segment is a polytetrahydrofuran segment, and the first flexible segment is a polyethylene glycol segment.

[0083] The electrode material additive provided by the present application includes a first polymer molecule 100 with a first matching segment at both ends, and a second polymer molecule 200 with a second matching group at both ends, which is connected by the topological bonding of the first matching segment and the second matching segment, and the first polymer molecule 100 passes through the cyclic group in the second polymer molecule 200, so that the first polymer molecule 100 and the second polymer molecule 200 form a non-chemically bonded mechanical interlocking mode, and the mechanical interlocking of the first polymer molecule 100 and the second polymer molecule 200 not only maintains the dynamic movement of the first polymer molecule 100 (free sliding in the case of mechanical interlocking of the ring structure), has efficient energy dissipation characteristics, greatly improves flexibility, and maintains high stability and strength without destroying covalent bonds. At the same time, the mechanical interlocking of the first polymer molecule 100 and the second polymer molecule 200, on the one hand, avoids the disadvantage that the molecular chain rotation of the electrode material additive is hindered due to the large molecular weight, and then the flexibility is reduced, and on the other hand, it also greatly improves the problem of insufficient toughness and susceptibility to electrolyte corrosion caused by the short chain of the electrode material additive.

[0084] In one embodiment, the second polymer molecule 200 further includes a second functional unit, which is connected to the other end of the second repeating unit, and the second functional unit is used to repair solid interface defects in the electrode material. Specifically, the second functional unit has a self-repairing property, so the second functional unit has good interface self-healing ability and can be used to repair solid interface defects in the electrode material, such as cracks, etc., thereby improving the solid interface structure stability in the electrode material. In a specific embodiment, the second functional unit may be different from the first functional unit.

[0085] In one embodiment, the second polymer molecule further includes a second self-repairing segment, and the second self-repairing segment is connected to one end of the second flexible segment away from the second matching segment. Therefore, two crown ether groups are included in the second polymer molecule 200. Therefore, the second polymer molecule 200 includes a second matching segment, a second flexible segment, a second self-repairing segment, a second flexible segment, and a second matching segment connected in sequence. Therefore, the second polymer molecule 200 can be topologically bonded to the two first polymer molecules 100 through the second matching segments at both ends.

[0086] In this embodiment, the molecular structure formula of the first polymer molecule 100 is [SH]-[EG1] n2 -[SS1]-[EG1] n2 -[SH], where [SH] is the first matching segment, [EG1] n2 is the first flexible segment, EG1 is the first repeating unit, [SS1] is the first self-healing segment, SH includes a steric end group, and SH and EG1 are connected via a nitrogen-containing group. The molecular structure formula of the second polymer molecule 200 is [CC]-[EG2] n3 -[SS2]-[EG2] n3 -[CC], where [CC] is the second matching segment, [EG2] n3 is the second flexible segment, EG2 is the second repeating unit, and [SS2] is the first self-repairing segment.

[0087] In one embodiment, the weight average molecular weight of the electrode material additive is 500 to 2500. Optionally, the weight average molecular weight of the electrode material additive may be 500, 1000, 1500, 2000, or 2500.

[0088] In one embodiment, the number of repeating units in the first soft segment is 4 to 46, that is, [EG1] in the above embodiment. n24≤n2≤46. Optionally, the number of repetitions of the first repeating unit may be 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 46; preferably, the number of repetitions of the first repeating unit may be 4-35.

[0089] In one embodiment, the number of repeating units in the second soft segment is 4 to 46, that is, [EG2] in the above embodiment. n3 4≤n3≤46. Optionally, the number of repetitions of the second repeating unit may be 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 46; preferably, the number of repetitions of the second repeating unit may be 4-35.

[0090] In one embodiment, the first self-repairing segment comprises an XX bond, wherein X is any element in group VIA. In a specific embodiment, the first self-repairing segment comprises an SS bond (disulfide bond), a Se-Se bond (diselenide bond), and the like.

[0091] In one embodiment, the second self-repairing segment comprises an XX bond, wherein X is any element in group VIA. In a specific embodiment, the second self-repairing segment comprises an SS bond (disulfide bond), a Se-Se bond (diselenide bond), and the like.

[0092] In one embodiment, the amount of the electrode material additive added to the electrode material is 0.05% to 0.3%. Optionally, the amount of the electrode material additive added to the electrode material can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%. The electrode material additive can improve the crack resistance and flexibility of the thick coating of the electrode piece, and will not affect the content of the electrode material.

[0093] This application provides a method for preparing an electrode material additive. Please refer to Figure 4 and Figure 5 .

[0094] In one embodiment, the preparation method of the electrode material additive comprises the following steps:

[0095] Step B10, preparing a mixed solution containing a first polymer molecular precursor, wherein the first polymer molecular precursor comprises a first coordination segment and a first flexible segment.

[0096] Step B20, adding a second polymer molecule to the mixed solution, the second polymer molecule comprising a second coordinating segment and a second flexible segment, the second coordinating segment comprising a cyclic group, the second coordinating segment being topologically bonded to the first coordinating segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanically interlocking chain to obtain an electrode material additive.

[0097] Specifically, in this embodiment, the molecular structures of the first polymer molecule and the second polymer molecule are different, so the electrode material additive includes multiple first polymer molecules and multiple second polymer molecules, and the multiple first polymer molecules and the multiple second polymer molecules are periodically connected together.

[0098] In one embodiment, in step B10, a mixed solution having a first polymer molecule precursor is prepared, specifically comprising: adding a flexible chain monomer A, a flexible chain monomer B and a steric monomer to a solvent for reaction, and controlling the solvent to be acidic, and stirring under a protective gas to obtain a first polymer molecule precursor comprising a first coordination segment and a first flexible segment. Wherein, the flexible chain monomer A and the flexible chain monomer B both comprise a first coordination segment and a first flexible segment, the first coordination segment connects the first flexible segment, and the steric monomer comprises a steric terminal group and an active group. The flexible chain monomer A reacts with the steric monomer to obtain a first polymer molecule precursor A, and the flexible chain monomer B reacts with the steric monomer to obtain a first polymer molecule precursor B, specifically, the active group of the flexible chain line reacts with the active group of the steric monomer to form the first coordination segment.

[0099] In one embodiment, in step B10, the flexible chain monomer A and the flexible chain monomer B can refer to the flexible chain monomers in the above embodiment, including NH2-PEG-COOH, NH2-PPG-COOH, NH2-PTMG-COOH, etc., which are not described in detail here. The first repeating unit molecular structure in the flexible chain monomer A and the flexible chain monomer B is the same, and the number of the first repeating units is the same or different.

[0100] In a specific embodiment, taking carboxyl and amino terminated polyethylene glycol as an example, the chemical formula of the flexible chain monomer A is NH2-(CH2CH2O) p-1 -CH2CH2-COOH, the chemical formula of the flexible chain monomer B is NH2-(CH2CH2O) q-1 -CH2CH2-COOH, where (CH2CH2O) p-1 or (CH2CH2O) q-1 [EG1] in the above embodiment n2 , 1≤p≤46, 1≤q≤46, 4≤p+q≤46.

[0101] In other embodiments, in step B10, the first flexible chain segments in the flexible chain monomer A and the flexible chain monomer B have different molecular structures, but the number of first repeating units is the same or different. For example, the chemical formula of the flexible chain monomer A is NH2-(CH2CH2CH2CH2O) p-1 -CH2CH2-COOH, the chemical formula of the flexible chain monomer B is NH2-(CH2CH2O)q-1 -CH2CH2-COOH.

[0102] In one embodiment, in step B10, the steric unit can also refer to the above embodiment, which is not described here. However, based on the flexible chain monomer A and the flexible chain monomer B, the obtained mixed solution includes two first polymer molecular precursors (first polymer molecular precursor A and first polymer molecular precursor B, respectively). However, the two first polymer molecular precursors are to obtain a main chain terminated with a steric end group containing an imino group.

[0103] In one embodiment, in step B20, before adding the second polymer molecule to the mixed solution, the second polymer molecule is prepared. Figure 5 , including:

[0104] Step B21, adding flexible chain monomer C and flexible chain monomer D into solvent A, adding hydroxyl activator and catalyst under protective atmosphere, drying after sufficient reaction to obtain flexible chain monomer E and flexible chain monomer F.

[0105] Step B22, adding the flexible chain monomer E, the flexible chain monomer F, the second self-healing monomer and the cyclic monomer into the solvent B, and adding a basic catalyst and stirring until all the monomers are completely reacted to obtain a second polymer molecule.

[0106] In one embodiment, in step B21, both the flexible chain monomer C and the flexible chain monomer D include the second flexible segment in the above embodiment, and the flexible chain monomer C or the flexible chain monomer D includes a polymer with double-terminal hydroxyl groups, including but not limited to double-terminal hydroxyl polyethylene glycol (HO-PEG-H), double-terminal hydroxyl polypropylene glycol (HO-PPG-H), double-terminal hydroxyl polytetrahydrofuran (HO-PTMG-H), etc. In addition, the second flexible segment molecular structure in the flexible chain monomer C and the flexible chain monomer D is the same, and the number of the second repeating units is the same or different.

[0107] In a specific embodiment, taking double-terminated hydroxyl polyethylene glycol as an example, the chemical formula of the flexible chain monomer C is HO-(CH2CH2O) x -H, the chemical formula of the flexible chain monomer D is HO-(CH2CH2O) y -H, where 1≤x<46, 1≤y<46, 4≤x+y<46.

[0108] In other embodiments, in step B21, the second flexible segment molecular structures in the flexible chain monomer C and the flexible chain monomer D are different, and the number of the second repeating units is the same or different. For example, the chemical formula of the flexible chain monomer C is HO-(CH2CH2CH2CH2O) x-H, the chemical formula of the flexible chain monomer D is HO-(CH2CH2O) y -H.

[0109] In other embodiments, in step B21, the flexible chain monomer C or the flexible chain monomer D may also include double-terminated hydroxyl polyether (HO-POP-OH), polyester (HO-PET-OH), polyurethane (HO-PU-OH), polysiloxane, etc.

[0110] In one embodiment, in step B21, solvent A comprises a mixed solution of toluene or tetrahydrofuran and water, the mass ratio of the organic solvent to water is 1:1, and the hydroxyl activator and the catalyst are added in batches under the protective atmosphere of an ice water bath (0°C to 5°C).

[0111] In one embodiment, in step B21, the hydroxyl activator includes any one of methanesulfonyl chloride (TsCl) and trifluoromethanesulfonate acetyl chloride (TfCl), and the catalyst includes any one of triethylamine, 4-dimethylaminopyridine (DMAP), KOH, and NaOH. Optionally, the hydroxyl activator can be added in batches, and the catalyst can also be added in batches to avoid excessive heat release.

[0112] In one embodiment, in step B21, the drying process after sufficient reaction specifically includes: after the addition of the hydroxyl activator and the catalyst is completed, reacting in an ice water bath for 3h to 4h, then extracting with dichloroethane and water, combining the organic phases, drying with anhydrous sodium sulfate or anhydrous magnesium sulfate, and finally spin drying at 80 to 100°C to obtain flexible chain monomer E and flexible chain monomer F.

[0113] In one embodiment, in step B21, the flexible chain monomer E or the flexible chain monomer F includes the second flexible segment in the above embodiment, and the flexible chain monomer E or the flexible chain monomer F includes a double-end activated polymer. For example, the chemical formula of the flexible chain monomer E is TsO / TfO-(CH2CH2O) x-1 -CH2CH2-OTs / OTf, the chemical formula of the flexible chain monomer F is TsO / TfO-(CH2CH2O) y-1 -CH2CH2-OTs / OTf, (CH2CH2O) x-1 or (CH2CH2O) y-1 [EG2] in the above embodiment n3 .

[0114] In one embodiment, in step B22, the second self-repairing monomer comprises a second self-repairing segment and an active group connected to both ends of the second self-repairing segment, wherein the second self-repairing segment comprises an XX bond, wherein X is any element in the VIA group. The second self-repairing monomer may be the same as or different from the first self-repairing monomer in the above embodiment, and will not be described in detail here.

[0115] In one embodiment, in step B22, the cyclic monomer is a crown ether derivative, specifically including but not limited to hydroxymethyl crown ether, including one or more of 2-(hydroxymethyl)-12-crown 4-ether, 2-(hydroxymethyl)-15-crown 5-ether, 2-(hydroxymethyl)-18-crown 6-ether, and 2-(hydroxymethyl)-21-crown 7-ether.

[0116] In one embodiment, in step B22, solvent B includes tetrahydrofuran and / or acetonitrile. The basic catalyst includes one or more of potassium carbonate, sodium hydride, and triethylamine. After adding the basic catalyst, the reaction is stirred at room temperature for 3 to 5 hours until the reaction is complete to obtain a second polymer molecule, and the molecular structure formula of the second polymer molecule is [CC]-[EG2] n3 -[SS2]-[EG2] n3 -[CC], where [CC] is the second matching segment, [EG2] n3 is the second flexible segment, EG2 is the second repeating unit, and [SS2] is the first self-repairing segment.

[0117] In one embodiment, in step B20, a second polymer molecule is added to the mixed liquid, specifically comprising: after the reaction in step B10 is completed, the second polymer molecule is added to the mixed liquid, and under the induction of the first coordinating segment, the cyclic groups at both ends of the second polymer molecule penetrate from the main chains of the two first polymer molecules respectively, and are topologically bonded to the first coordinating segment.

[0118] In one embodiment, in step B20, after adding the second polymer molecule to the mixed liquid, it also includes: adding a first self-healing monomer to the mixed liquid after the reaction is completed, and the first self-healing monomer reacts with the first polymer molecule precursor to obtain a first polymer molecule with a first coordinating chain segment at both ends.

[0119] It should be explained that the first self-healing monomer reacts with the first polymer molecule precursor, and the first polymer molecule precursor contains exposed active groups (carboxyl groups), so the active groups (hydroxyl groups) at both ends of the first self-healing monomer can undergo esterification reaction with the two first polymer molecule precursors respectively to obtain ester groups.

[0120] In one embodiment, in step B20, the self-assembly time of the first polymer molecule precursor and the second polymer molecule can be 0.5h to 3h.

[0121] In one embodiment, in step B20, an appropriate amount of concentrated sulfuric acid / concentrated phosphoric acid may be added at the same time as the first self-healing monomer is added, and the precursor in the mixed solution is allowed to fully react for 4 hours to 6 hours.

[0122] In one embodiment, in step B20, after the reaction is completed, an appropriate amount of dichloroethane is added to the mixed solution for extraction, the organic phases are combined, dried with anhydrous sodium sulfate or anhydrous magnesium sulfate, and finally spin-dried at 80° C. to 100° C. to obtain the electrode material additive.

[0123] The present application prepares another electrode material additive through the above-mentioned preparation method, which can be applied to the aqueous or organic solvent of the electrode material to improve the flexibility of the electrode and prevent the electrode from cracking. The electrode material additive includes a first polymer molecule with a double steric end, and its two ends include two first matching segments, and also includes a bicyclic second polymer molecule, and its two ends include two second matching segments, and the two are connected linearly and periodically by topological bonding. Both ends of each first polymer molecule are independently mechanically interlocked with a second polymer molecule, and both ends of each second polymer molecule are independently mechanically interlocked with a first polymer molecule, and the second polymer molecule can slide freely on the flexible main chain of the first polymer molecule (molecular pulley) without falling off, thereby forming a mechanically interlocked linear necklace structure.

[0124] The present application also provides a pole piece.

[0125] In one embodiment, the electrode sheet includes an electrode material and an electrode material additive provided in the above embodiment, and the electrode material is a positive electrode material or a negative electrode material. Among them, the positive electrode material can reversibly deintercalate active lithium ions, and the active lithium ions migrate between the positive electrode and the negative electrode of the battery to realize battery charging and discharging. The positive electrode material can be a phosphate positive electrode material and a ternary positive electrode material. Exemplarily, the positive electrode material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate oxygen, fluoro vanadium phosphate lithium, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. And a lithium supplement material can be added to the positive electrode material. Exemplarily, the lithium supplement material can be lithium iron-rich lithium, lithium cobalt-rich lithium, lithium nickel-rich lithium, etc.

[0126] In one embodiment, after adding the electrode material additive, the limiting surface density of the single-sided electrode is 25 mg / cm 2 ~80mg / cm 2 ; Single-sided pole piece (pole piece surface density is set at 18mg / cm 2) The softness value tested by the softness tester is 400mN~950mN (the smaller the value, the softer the sample).

[0127] The present application also provides a secondary battery.

[0128] In one embodiment, the secondary battery can be a composition system commonly used in the prior art, for example including a negative electrode plate, an electrolyte membrane and a positive electrode plate. The electrolyte can be a solid electrolyte or a liquid electrolyte. When a solid electrolyte is selected, the use of a diaphragm can be adaptively selected; both the positive electrode plate and the negative electrode plate can include the electrode material additives provided above.

[0129] The technical solution of the present application is described in detail below through specific embodiments.

[0130] Example 1

[0131] The present embodiment provides an electrode material additive, which includes a polymer molecule, which includes a first cooperating segment, a first flexible segment, a first self-healing segment and a second cooperating segment connected in sequence, wherein the first cooperating segment includes a steric end group (benzene ring), and the cyclic group in the second cooperating segment serves as a capping group at the other end.

[0132] Among them, the weight average molecular weight of the electrode material additive is about 1500, the repetition number of the first repeating unit in the first flexible segment is 21 to 22, and the first self-healing segment contains SS bonds.

[0133] The preparation method of the electrode material additive provided in this embodiment is as follows:

[0134] 1) 1 part of polyethylene glycol (COOH-(CH2CH2O) n1 -CH2CH2-NH2, n1 is 21-22, Mw ~ 1000) in an aqueous solution, the solution is adjusted to pH 2 with hydrochloric acid and ammonium hexafluorophosphate, stirred under protective gas N2 and 70 ° C, and 1 part of benzaldehyde is slowly added to perform end-capping reaction for 3 hours to obtain a cation-containing amino NH 2+ The polyether main chain is terminated with benzene rings.

[0135] 2) maintaining the same temperature as step 1), after the reaction in step 1) is completed, add 1 part of 4-carboxybenzo-12-crown-4, the cyclic structure of 12-crown-4 in the positive ion NH 2+ Under the induction, the carboxyl end of the flexible main chain penetrates into the NH 2+The self-assembly complex was carried out for 2 hours. One part of bis(2-hydroxyethyl) disulfide and an appropriate amount of concentrated sulfuric acid were added, and the carboxyl group of 4-carboxybenzo-12-crown ether-4 and the carboxyl group of the benzene ring-terminated polyether main chain reacted with the hydroxyl group of bis(2-hydroxyethyl) disulfide for 5 hours to carry out esterification and dehydration. After the reaction, dichloroethane and water were used for extraction, and the organic phases were combined and dried with anhydrous magnesium sulfate. Finally, the electrode material additive was obtained by spin drying at 80°C. The chemical structure of the polymer molecule is as follows: Figure 1 See also Figure 6 In the figure, peak a (hump, 3400-3500cm-1) is the stretching vibration absorption peak of the secondary amine -NH- in the polymer main chain; peak b (double hump, 2800-3000cm-1) is the symmetrical stretching vibration peak of -CH2- and -CH-, and peak e (1460cm-1) is the bending vibration absorption peak of -CH2-; peak c (double peak, 1725cm-1, 1716cm-1) is the carbonyl absorption peak of o-phenyl ester, respectively. The vibration absorption peaks of C=O and carbonyl C=O of non-o-phenyl ester; the d peak (1548cm-1) is the vibration absorption peak of the benzene ring; the f peak (three peaks, 1050cm-1, 1100cm-1, 1175cm-1) is the stretching vibration peak of the main chain polyether -COC, and the g peak (945cm-1) is the alicyclic ether, that is, the -COC- stretching vibration peak of the ring; the h peak (558-1) is the vibration absorption peak of the disulfide bond SS.

[0136] Example 2

[0137] This embodiment provides an electrode material additive, and the difference between this embodiment and embodiment 1 is that the weight average molecular weight of the electrode material additive is about 2600. In step 1) of the preparation method, 1-pyrene carboxaldehyde is used to replace benzaldehyde, and the number of repetitions of the first repeating unit in the first soft segment is 43-44.

[0138] Example 3

[0139] This embodiment provides an electrode material additive. The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the electrode material additive is about 2800, and the number of repetitions of the first repeating unit in the first soft segment is 50-51.

[0140] Example 4

[0141] This embodiment provides an electrode material additive. The difference between this embodiment and Embodiment 1 is that the first self-repairing segment contains a Se-Se bond.

[0142] Example 5

[0143] This embodiment provides an electrode material additive. The difference between this embodiment and embodiment 1 is that the first flexible segment is a polycaprolactone segment, and the chemical formula of the first flexible segment is (C6H 10O2) n .

[0144] Example 6

[0145] This embodiment provides an electrode material additive. The difference between this embodiment and embodiment 1 is that the monomer of the first coordination segment is 4-carboxybenzo-15-crown-5.

[0146] Example 7

[0147] This embodiment provides an electrode material additive. The difference between this embodiment and Embodiment 1 is that the first self-repairing segment is replaced by a polymer segment containing an OO bond.

[0148] Example 8

[0149] The present embodiment provides an electrode material additive, which includes a first polymer molecule and a second polymer molecule, wherein the first polymer group includes a steric end group, a first coordination segment, a first repeating unit, a first functional unit, a first repeating unit, a first coordination segment and a steric end group connected in sequence, and the second polymer molecule includes a second coordination segment, a second repeating unit, a second functional unit, a second repeating unit and a second coordination segment connected in sequence.

[0150] Among them, the weight average molecular weight of the electrode material additive is about 1500, the weight average molecular weight of the first polymer molecule is about 1500, the weight average molecular weight of the second polymer molecule is about 1500, the sum of the repetition numbers of the first repeating unit in the first flexible segment is 25 to 26, the first self-healing segment contains SS bonds, the sum of the repetition numbers of the second repeating units in the second flexible segment is 21 to 22, and the second self-healing segment contains SS bonds.

[0151] The preparation method of the electrode material additive provided in this embodiment is as follows:

[0152] 1) 1 part of double-terminated hydroxyl polyethylene glycol (HO-(CH2CH2O) x -H), and another double-terminated hydroxyl polyethylene glycol (HO-(CH2CH2O) y -H) is dissolved in a mixed solvent of toluene and water (1:1), wherein 1≤x≤21, 1≤y≤21, 21≤x+y≤22. In an ice-water bath under N2 protection (0°C), 2 parts (total amount) of methanesulfonyl chloride and 0.02 parts (total amount) of catalyst 4-dimethylaminopyridine are slowly added in 4 batches, once every 0.5h. After the entire feeding process is completed, continue to react in an ice-water bath for 3h. After the reaction is completed, extract with dichloroethane and water, combine the organic phases, dry with anhydrous sodium sulfate, and finally spin-dry at 90°C to obtain the product TsO-(CH2CH2O) x-1-CH2CH2-OTs and TsO-(CH2CH2O) y-1 -CH2CH2-OTs.

[0153] 2) Disperse 2 parts of the product in step 1), 1 part of bis(2-hydroxyethyl) disulfide and 2 parts of 2-(hydroxymethyl)-12-crown 4-ether in tetrahydrofuran, add 0.03 parts of triethylamine as a catalyst, and stir the reaction at room temperature for 5 hours until the reaction is complete to obtain a second polymer molecule.

[0154] 3) 1 part of amine- and carboxyl-terminated polyethylene glycol (NH2-(CH2CH2O) p-1 -CH2CH2-COOH), and another portion of amine- and carboxyl-terminated polyethylene glycol (NH2-(CH2CH2O) q-1 -CH2CH2-COOH) was dissolved in water, where 1≤p≤25, 1≤q≤25, 25≤p+q≤26. The pH was adjusted to 3 with hydrochloric acid and ammonium hexafluorophosphate, stirred under protective gas N2 at 70°C, and 2 parts of benzaldehyde were slowly added to perform end-capping reaction for 3 hours to obtain a cation-containing amino group NH 2+ The polyether main chain is terminated with benzene rings.

[0155] 4) After the reaction in step 3) is completed, one part of the second polymer molecule in step 2) is added. The second polymer molecule is in the positive ion NH 2+ Under the induction, the carboxyl end of the flexible main chain penetrates into the NH 2+ The self-assembly complex was carried out for 2 hours. One part of bis(2-hydroxyethyl) disulfide and an appropriate amount of concentrated sulfuric acid were added, and the carboxyl group of the sterically blocked polyether chain reacted with the hydroxyl group of bis(2-hydroxyethyl) disulfide for 5 hours to carry out esterification and dehydration. After the reaction, dichloroethane and water were used for extraction, and the organic phases were combined and dried with anhydrous magnesium sulfate. Finally, the electrode material additive was obtained by spin drying at 90°C. The chemical structures of the first polymer molecule and the second polymer molecule are as follows: Figure 3 shown.

[0156] Example 9

[0157] This embodiment provides an electrode material additive, and the difference between this embodiment and embodiment 8 is that the weight average molecular weight of the electrode material additive is 2500. In step 3) of the preparation method, 1-pyrene carboxaldehyde is used to replace benzaldehyde, and the number of repetitions of the first repeating unit in the first soft segment is 66-67.

[0158] Example 10

[0159] This embodiment provides an electrode material additive. The difference between this embodiment and embodiment 7 is that the weight average molecular weight of the electrode material additive is about 2760, the number of repetitions of the first repeating unit in the first flexible segment is 55 to 56, and the number of repetitions of the second repeating unit in the second flexible segment is 53 to 54.

[0160] Embodiment 11

[0161] This embodiment provides an electrode material additive. The difference between this embodiment and Embodiment 8 is that the first self-repairing segment contains a Se-Se bond, and the second self-repairing segment contains a Se-Se bond.

[0162] Comparative Example 1

[0163] This comparative example provides a polyvinyl alcohol-based flexible additive for electrode materials available on the market.

[0164] Comparative Example 2

[0165] This comparative example provides an electrode material additive, and the electrode material additive includes a mechanically interlocking polymer. The preparation method of the electrode material additive provided in this comparative example is as follows:

[0166] 1) In a round-bottom flask, 10 mmol of polyglycol, 20 mmol of 4-toluenesulfonyl chloride, 20 mmol of sodium hydroxide and 400 mL of tetrahydrofuran were added in sequence, and magnetic stirring was performed under nitrogen protection for 12 h to obtain a light yellow suspension. The reaction solution was filtered to obtain a crude product, which was then washed with deionized water and dried over anhydrous sodium sulfate, and filtered again to obtain product A.

[0167] 2) 7 mmol of product A and 17.5 mmol of methyl 3,4-dihydroxybenzoate were dissolved in 200 mL of acetonitrile, and the organic solvent was removed after the reaction, and product B was obtained after hydrolysis; wherein the reaction temperature was 80° C. and the reaction time was 24 h.

[0168] 3) In a round-bottom flask with a condenser, 7 mmol of product B, 7 mmol of p-hydroxybenzaldehyde and 140 mL of methanol were added in sequence, and stirred at room temperature for 12 h under nitrogen protection to obtain a yellow suspension. Subsequently, 7 mmol of 1-aminopentene was added and the temperature was raised to 80°C. The reaction was continued with stirring for 12 h. After the reaction was completed, the mixture was cooled to room temperature and the organic solvent was removed to obtain a crude product. The crude product was dissolved in 50 mL of dichloromethane, and 5 mL of hydrochloric acid and 20 mL of ammonium hexafluorophosphate aqueous solution were added in sequence. After stirring at room temperature for 6 h, the organic solvent was removed to obtain a colorless viscous liquid, which was product C.

[0169] 4) In a round-bottom flask with a condenser, 5 mmol of α-acetyl-γ-butyrolactone, 10 mmol of guanidine carbonate, 22 mL of triethylamine, 10 mL of cystamine dihydrochloride and 80 mL of anhydrous ethanol were added in sequence, and magnetic stirring was performed under nitrogen protection. After heating and reflux for 8 h to obtain a light yellow precipitate, heating was stopped. The reaction solution was filtered and the residue was collected to obtain a crude product, which was then washed with anhydrous ethanol and acetone in sequence. After filtering again, the filter cake was placed in a 50°C vacuum drying oven and dried for 12 h to obtain a white solid powder, i.e., a quadruple hydrogen bond (ureidopyrimidone) compound D.

[0170] 5) The purified product C and product D were dissolved in 20 mL of N,N-dimethylformamide (DMF), and a free radical initiator (triaryl siloxane) was added under stirring. After reacting for 1 hour, a mechanical interlocking polymer was obtained.

[0171] Comparative Example 3

[0172] N-methylpyrrolidone (NMP) was used to replace the electrode material additive.

[0173] The electrode material additive parameters provided by Examples 1 to 11 and Comparative Examples 1 to 3 are shown in Table 1:

[0174] Table 1 Electrode material additive parameters provided in Examples and Comparative Examples

[0175] Group Name Weight average molecular weight of electrode material additives The number of the first repeating unit The number of the second repeating unit Example 1 1500 21~22 - Example 2 2600 42~43 - Example 3 2800 50~51 - Example 4 1600 21~22 - Example 5 1750 10~11 - Example 6 1550 21~22 - Example 7 1350 21~22 - Example 8 1500 25~26 21~22 Example 9 2500 66~67 21~22 Example 10 2760 55~56 53~54 Embodiment 11 1600 25~26 21~22 Comparative Example 1 6250 - - Comparative Example 2 - - - Comparative Example 3 - - -

[0176] The electrode material additives provided in the above Examples 1-11 and the electrode material additives provided in Comparative Examples 1-3 are respectively prepared into positive electrode slurries, positive electrode sheets and lithium ion batteries according to the following methods:

[0177] A method for preparing a lithium ion battery comprises the following steps:

[0178] 1) Preparation of positive electrode sheet: 96.5g lithium iron phosphate DY-12, 1.3g Super P, 2.2g positive electrode binder, 1.93g electrode material additive (the amount of additive added is 0.02% (mass fraction) of the main active material) and 76.64g NMP are mixed, and the positive electrode slurry is obtained by degassing machine, the dispersion time is 30min, the rotation speed is 2000rpm, the positive electrode slurry is coated on the opposite sides of the aluminum foil, after rolling, vacuum drying at 120°C overnight to obtain a positive electrode sheet. Among them, the positive electrode binder is the electrode material additive of each embodiment or comparative example.

[0179] 2) Preparation of negative electrode sheet: 95g of graphite, 2g of Super P, 0.5g of carboxymethyl cellulose, and 2.5g of styrene-butadiene rubber (SBR) were placed in deionized water and mixed evenly to prepare negative electrode slurry, and the negative electrode slurry was coated on the opposite sides of the copper foil. After drying-rolling-secondary drying process, the negative electrode sheet was obtained.

[0180] 3) Preparation of electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (DEC) were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L.

[0181] 4) Secondary battery (lithium-ion battery) assembly: Lithium-ion batteries are assembled in an argon inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0182] The materials and products provided in the above Examples 1-11 and the materials and products provided in Comparative Examples 1-3 were tested as follows. The test results are shown in Tables 2 and 3:

[0183] 1. Test of the softness of the positive electrode: GB / T 8942 "Determination of paper softness" is used to test the positive electrode. The test principle is that under specified conditions, when the plate probe presses the sample into the slit to a certain depth (10mm), the instrument records the sum of the bending resistance of the sample itself and the maximum vector of the friction force between the sample and the slit, which is called the softness of the sample. The smaller the instrument reading, the softer the sample. The surface density of the positive electrode is set at 18mg / cm 2 .

[0184] 2. Test of the limiting surface density of the positive electrode: The slurry is coated according to different coating scales. According to the maximum mass of the coated positive electrode without cracking, repeat the test for 3 groups, take the average value, and then perform surface density conversion to obtain the maximum surface density value.

[0185] 3. Positive electrode resistivity test: Use the four-probe method to test the positive electrode. Use four equally spaced probes to pierce the surface of the semiconductor. A constant current source provides a suitably small current I to the two outer probes. Then the voltage V between the two middle probes is measured to determine the resistivity of the semiconductor.

[0186] 4. Lithium-ion battery performance test: Observe the first cycle charge and discharge capacity of the battery at 0.1C at room temperature (25±3℃).

[0187] 5. Test of lithium-ion battery cycle stability: In a room temperature (25±3℃) environment, cycle 400 times at 1C rate and observe the change in battery capacity.

[0188] Table 2 Test results of positive electrode sheets corresponding to various embodiments and comparative examples

[0189]

[0190]

[0191] Table 3 Test results of lithium-ion batteries corresponding to various embodiments and comparative examples

[0192]

[0193] It can be seen from the test results of the embodiments and comparative examples in Table 2 that the softness of the positive electrode sheets provided in the embodiments of the present application is less than 900mN, which is much smaller than the positive electrode sheets provided in the comparative examples. Compared with the commonly used electrode material additives on the market (Comparative Example 1) and other polymers with mechanical interlocking (Comparative Example 2), it is shown that the softness value of the positive electrode sheets provided in the present application is greatly reduced, and the flexibility is significantly improved; the softness of the positive electrode sheets provided in the present application is far superior to the positive electrode sheets without additives (Comparative Example 3). In addition, the resistivity of the positive electrode sheets provided in the embodiments of the present application is smaller than that of the positive electrode sheets provided in the comparative examples, indicating that the electrode material additives of the present application will not affect the electrical properties of the positive electrode sheets. Moreover, the limiting surface density and peel strength of the positive electrode sheets provided in the embodiments of the present application are greater than those of the positive electrode sheets provided in the comparative examples. Therefore, it is shown that the positive electrode sheets prepared by adding the electrode material additives prepared by the scheme provided in the present application to the positive electrode slurry have excellent physical properties, that is, the electrode material additives can solve the problem of cracking caused by insufficient toughness of the sheets. Please also refer to Figure 7 , Figure 7 The electrode state of Example 1 at the limit surface density is shown in FIG. 1. It can be seen that Example 1 is 68.4 g / cm 2 There is no crack at the surface density of 38g / cm 2 Micro cracks will occur at a surface density of 50.5g / cm 2 The prepared coating showed multiple cracks and could not be used.

[0194] It can be seen from the test results of the embodiments and comparative examples in Table 3 that the lithium-ion battery prepared by the positive electrode plate also has excellent electrical properties, indicating that the electrode material additive provided in the present application has little effect on the electrical properties of the battery, and can solve the problem of cracking caused by insufficient toughness of the electrode plate while ensuring battery performance.

[0195] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0196] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. An electrode material additive, characterized in that: The invention comprises a first polymer molecule and a second polymer molecule, wherein the first polymer molecule comprises a first matching segment and a first flexible segment connected to each other, the second polymer molecule comprises a second matching segment and a second flexible segment connected to each other, the second matching segment comprises a cyclic group, and the second matching segment is topologically bonded to the first matching segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanically interlocked chain.

2. The electrode material additive according to claim 1, characterized in that: The first polymer molecule and the second polymer molecule have the same molecular structure, the first flexible segment and the second flexible segment have the same molecular structure, both ends of the first flexible segment are connected to the first matching segment and the second matching segment respectively, and a plurality of the first polymer molecules or a plurality of the second polymer molecules form a mechanical interlocking chain connected in sequence; or The molecular structures of the first polymer molecule and the second polymer molecule are different, the two ends of the first flexible segment are respectively connected to a first matching segment, the two ends of the second flexible segment are respectively connected to a second matching segment, and the first polymer molecule and the second polymer molecule form a periodically connected mechanical interlocking chain.

3. The electrode material additive according to claim 2, characterized in that: The first polymer molecule further includes a first self-repairing segment, which is connected to an end of the first flexible segment facing away from the first matching segment.

4. The electrode material additive according to claim 3, characterized in that: The molecular structures of the first polymer molecule and the second polymer molecule are different. The second polymer molecule further includes a second self-repairing segment, and the second self-repairing segment is connected to an end of the second flexible segment away from the second matching segment.

5. The electrode material additive according to claim 4, characterized in that: The first coordination segment includes a nitrogen-containing group, the second coordination segment includes a crown ether group, the crown ether group is arranged around the periphery of the nitrogen-containing group, the first self-healing segment and / or the second self-healing segment contains an XX bond, wherein X is any element in the VIA group.

6. The electrode material additive according to any one of claims 1 to 5, characterized in that: The first matching segment includes a steric end group, which is used to end-cap the first polymer molecule. The cyclic group is the end group of the second polymer molecule, which is used to end-cap the second polymer molecule.

7. The electrode material additive according to any one of claims 1 to 6, characterized in that: The weight average molecular weight of the electrode material additive is 500 to 2500; and / or The number of repeating units in the first flexible segment is 4 to 46; and / or The number of repeating units in the second flexible segment is 4-46.

8. A method for preparing an electrode material additive, characterized in that: The preparation method comprises the following steps: Preparing a mixed solution having a first polymer molecular precursor, wherein the first polymer molecular precursor comprises a first coordination segment and a first flexible segment; A second polymer molecule or a second polymer molecule precursor is added to the mixed liquid, wherein the second polymer molecule and the second polymer molecule precursor both contain a second coordinating segment and a second flexible segment, the second coordinating segment contains a cyclic group, and the second coordinating segment is topologically bonded to the first coordinating segment through the cyclic group, so that the first polymer molecule and the second polymer molecule form a mechanically interlocking chain to obtain an electrode material additive.

9. A pole piece, characterized in that: The method comprises an electrode material and an electrode material additive as claimed in any one of claims 1 to 7, wherein the electrode material is a positive electrode material or a negative electrode material.

10. A secondary battery, characterized in that: The electrode sheet as claimed in claim 9 or the secondary battery comprises the electrode material additive as claimed in any one of claims 1 to 7.